Kemplang Panggang and Salted Fish as Potential Issues in Physics e-Module: An Effort to Enhance Students’ Creative Thinking Skills - Fitonia, Allika; Wiyono, Ketang; Sriyanti, Ida (Jurnal Pendidikan MIPA, 2024)
Abstract: This study aims to produce a physics e-module based on the local wisdom of kemplang panggang and salted fish to help improve the creative thinking skills of senior high school students. Three stages of Rowntree's development model, namely planning, development, and evaluation with Tessmer's formative evaluation technique were applied in this study. A total of twenty-eight of eleventh grade students from SMAN 1 Tanjung Batu were selected purposively as research participants. Students' creative thinking skills were measured using the creative thinking skills test and analyzed using the normalized gain formula. The results showed that the average pretest and posttest scores of students were 28.20 and 71.65 with an average n-gain value of 0.6. The results of the study concluded that the use of e-modules based on the local wisdom of kemplang panggang and salted fish was quite effective in improving students' creative thinking skills.        Keywords: physics e-module, local wisdom, creative thinking skill. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp453-467